ANTHROPOLOGY AND HEALTH IN COSTA RICA: DEGREE AND POSTGRADE FINAL PROJECTS - Quesada Cordero, Carolina (2014)
This article analyses issues, methods and theories developed in the graduate and postgraduateresearch projects related to health and disease, in the University of Costa Rica. Theanalysis seeks to contribute to the characterization of the medical Anthropology or theAnthropology health developed in Costa Rica. Also, it shows a series of possible researchtopics for future projects.